Improving household fish and vegetable availability through participation of rural women: A case study - S. Tanuja; A. Sarkar; G. Moharana; C. S. Mhatre (Indian Journal of Fisheries, 2023)
Homestead integrated aquaculture has immense potential towards alleviating poverty and undernourishment. In order to have sustainable and equitable impacts through small holder aquaculture innovations, a focus on gender being included at the very start of the design and dissemination is required. The present case study showcases the impact of gender inclusive interventions in improving the participation of women in homestead aquaculture, thereby improving the household fish and vegetable availability and income. Conservation of the diminishing stock of small indigenous fishes by deliberately farming them along with the Indian major carps (IMCs) was also a focus of the study. A gender inclusive approach was adopted in the capacity building of women on scientific aquaculture management practices. Twenty four homestead ponds having areas ranging from 0.17-0.22 ha in Puri District, Odisha covering a total area of 4 ha from four villages were selected to undertake participatory action research. The ponds were stocked with IMCs @10000 ha-1 and small indigenous fishes like Amblyphanrynogon mola and Puntius spp. @25000 ha-1. Several women friendly interventions like gillnets (mesh size 12 mm) a passive fishing gear and trellis system around pond bund for growing climber vegetables were introduced in the villages with an aim to improve the participation of women in homestead integrated aquaculture. As a result of the interventions, the fish production increased from 0.75 t ha-1 yr-1 to 2.48 t ha-1 yr-1. The involvement of women in harvesting of small fish using passive gear like gillnets and traps resulted in regular fortnightly availability of around 750 g of small micronutrient rich fish to rural families. The utilisation of pond bund for growing vegetables following the cropping calendar resulted in production around 790 kg vegetables per hectare of pond area. The study showed that women can immensely contribute to increasing and stabilising family income and in improving family nutrition by participating in homestead integrated aquaculture. The research also proved that polyculture of IMCs with small indigenous fishes by following the scientific management practices will result in better yield, improved fish availability to the house and better management of the household resources. Keywords: Aquaculture, Empowerment, Household, Horticulture, Participation, Women